Oral Glutamine in Preventing Treatment‐Related Mucositis in Adult Patients With Cancer: A Systematic Review. (27th October 2015) - Sayles, Caitlin; Hickerson, Stephen C.; Bhat, Raksha R.; Hall, Jacob; Garey, Kevin W.; Trivedi, Meghana V.
Abstract : Background: Breakdown of the mucosal barrier resulting in mucositis is a common adverse event in patients with cancer receiving chemotherapy and radiation. Many studies have evaluated the use of oral glutamine to prevent mucositis in these settings, but current guidelines make no recommendations with regard to its use. Our objective was to systematically review the evidence for the use of oral glutamine in preventing mucositis in adult patients with cancer undergoing chemotherapy and/or radiation. Materials and Methods: A systematic search of English‐language literature was done via MEDLINE using the search terms glutamine, cancer, and mucositis or esophagitis or stomatitis . Fifteen studies conducted in adult patients with cancer receiving chemotherapy and/or radiation comparing single‐agent oral glutamine with control were identified. Results: Oral glutamine was shown to be effective in 11 of the 15 studies included in the systematic review. It significantly reduced the incidence of grade 2, 3, or 4 mucositis and/or reduced weight loss as well as the duration, time of onset, and/or maximum grade of mucositis. The most common dosing regimen was 30 g/d in 3 divided doses, with other regimens ranging from 7.5–24 g/d. Rates of nausea, vomiting, dry mouth, and anorexia were similar in the glutamine and control groups. Conclusion: In summary, the favorable efficacy and low toxicity of oral glutamine observed in clinical trials we reviewed provide a strong rationale for large randomized placebo‐controlled studies to further evaluate its efficacy in preventing mucositis in patients with cancer receiving chemotherapy and/or radiation.